Totemism - Gendrolis, Edmundas (Problemos, 1986)
Totemism almost never played an independent role in the life of pre-class society. In various ways it was interweaved with such forms of consciousness as animism, magic, cult of ancestors and others. The consciousness of the society presented itself as a complex of all those forms. The article discusses various forms of totemism. Every one of them played different role in the particular societies. This explains why there is no independent definition of totemism. The author of the article defines totemism as a system of actions of social group. He views the basis of the system in the supposed mystic interrelation between the group and animals, plants, and other material objects, having life significance. However, even such a definition is incomplete: some totems do not play any important role in the life of society. Totemism as a component of the mythical world outlook can be singled out only as a relatively independent phenomena.